GE_GERICHTE C/24576/2013 vom 11. Dezember 2018 - GE Cour de justice (2018)
PACTE SUCCESSORAL ; INTERPRÉTATION(SENS GÉNÉRAL) ; ACTION EN RÉDUCTION ; RAPPORT SUCCESSORAL | CPC.230.al1; CC.494.al3; CC.495; CC.528.al1